Historical review of the fiscal system (Financial Reform Association, 1884)
Contains section XXVII(2nd part)-XXIX, continued from tract no. 31. - Orig. publ. as tract no. 35. - Issued 1851 by the Liverpool Financial Reform Association. - Authorship claimed by Alexander Somerville. - Repr. - In pamphlet volume with title on spine: Financial reform tracts : 1848-51.